Taxonomic notes on the Psephellus zuvandicus group (Asteraceae) from Iran - Ranjbar, Massoud; Negaresh, Kazem (Phytotaxa, 2014)
Psephellus khalkhalensis (Asteraceae) is described and illustrated as a new species of Psephellus sect. Psephellus from NW Iran. The section contains plants characterized by having often ascending or prostrate stems with few branches and a central rosette of leaves, lyrate to pinnatisect leaves, with arachnoid indumentum on the upper side, densely tomentose on the lower, appendages membranous, triangular to ovate, ciliate, without prominent terminal mucro or spinule, not decurrent, flowers purple or the central whitish. The new species is closely related to P. zuvandicus native to Iran, but differs from it by the shape of stem (decumbent or arcuate-ascending vs. ascending rarely erect), basal leaves [segments in 9–11 pairs, narrowly oblong, sometimes triangular, 2–4 mm wide vs. segments in 3–7 pairs, lanceolate or obovate, 5–12(–20) mm wide], colour of appendages (brown-blackish vs. pale brown), and also cilia (brownish vs. whitish). The value and utility of leaf indumentum was also evaluated as an additional source of information for the taxonomy of P. zuvandicus and P. khalkhalensis.